Critical Review of the State-of-the-Art on Lumbar Percutaneous Cement Discoplasty - Techens, Chloé; Eltes, Peter Endre; Lazary, Aron; Cristofolini, Luca (Frontiers in Surgery, 2022)
Interbody fusion is the gold standard surgery to treat lumbar disc degeneration disease but can be a high-risk procedure in elderly and polymorbid patients. Percutaneous Cement Discoplasty (PCD) is a minimally invasive technique developed to treat advanced stage of disc degeneration exhibiting a vacuum phenomenon. A patient-specific stand-alone spacer is created by filling the disc with polymethylmethacrylate cement, allowing to recover the disc height and improve the patient’s conditions. As it has recently been introduced in the lumbar spine, this review aims to present a transversal state-of-the-art of the surgery from its clinical practice and outcome to biomechanical and engineering topics. The literature was searched across multiple databases using predefined keywords over no limited period of time. Papers about vertebroplasty were excluded. Among 42 identified papers, the relevant ones included nine clinical papers reporting the variations of the surgical technique, follow up and complications, three papers reporting biomechanical ex vivo tests, and two letters related to published clinical papers. Papers presenting the operative practice are reported, as well as follow-ups up to two years. The papers found, consistently reported that PCD significantly improved the clinical status of the patients and maintained it after two years. Spine alignment was impacted by PCD: the sacral slope was significantly reduced, and disc height increased. The foramen opening correlated to the volume of injected cement. A substitute to the acrylic cement exhibited better osteointegration. Finally, limitations and risks of the surgery are discussed as well as potential improvements such as the development of new filling materials with better mechanical properties and biological integration or the investigation of the inner disc.